2016
DOI: 10.1128/jcm.01810-16
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Minocycline Susceptibility Testing Methods for Carbapenem-Resistant Acinetobacter baumannii

Abstract: cTreatment options for infections due to carbapenem-resistant Acinetobacter baumannii are extremely limited. Minocycline is a semisynthetic tetracycline derivative with activity against this pathogen. This study compared susceptibility testing methods that are used in clinical microbiology laboratories (Etest, disk diffusion, and Sensititre broth microdilution methods) for testing of minocycline, tigecycline, and doxycycline against 107 carbapenem-resistant A. baumannii clinical isolates. Susceptibility rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
3
9
1
Order By: Relevance
“…The results for minocycline look promising with EA and CA greater than 92% and no VMEs. These results are similar to those recently reported by Wang et al when testing 107 CRAB isolates against the tetracyclines using Etest, disk diffusion, and Sensititre BMD methods ( 67 ). VMEs (2.8%) were higher than in the present study ( 67 ).…”
Section: Discussionsupporting
confidence: 91%
“…The results for minocycline look promising with EA and CA greater than 92% and no VMEs. These results are similar to those recently reported by Wang et al when testing 107 CRAB isolates against the tetracyclines using Etest, disk diffusion, and Sensititre BMD methods ( 67 ). VMEs (2.8%) were higher than in the present study ( 67 ).…”
Section: Discussionsupporting
confidence: 91%
“…In one study, which evaluated the performance of Spanish laboratories to accurately determine A. baumannii AST results, minor errors of 88.6% were observed across all systems evaluated (14). A second study demonstrated minor errors of 15% to 40% across different disk diffusion, Sensititre, and Etest methods (15).…”
Section: Resultsmentioning
confidence: 93%
“…Sensitivities of minocycline, polymyxin B, colistin and phosphomycin were determined according to CLSI criteria (7). For the minocycline, the zone was considered sensitive if the diameter was ≥ 16 mm, moderately sensitive between 13 and 15 mm, and resistant if ≤ 9 mm (8).…”
Section: Methodsmentioning
confidence: 99%